KATP channels in mesenchymal stromal stem cells: strong up-regulation of Kir6.2 subunits upon osteogenic differentiation - Diehlmann, Anke; Bork, Simone; Saffrich, Rainer; Veh, Rüdiger W.; Wagner, Wolfgang; Derst, Christian (Tissue and cell, 2011)
The promising use of mesenchymal stromal cells (MSC) in regenerative technologies accounts for necessity of detailed study of their physiology. Proliferation and differentiation of multipotent cells often involve changes in their metabolic state. In the present study, we analyzed the expression of ATP-sensitive potassium (KATP) channels in MSC and upon in vitro differentiation. KATP channels are present in many cells and regulate a variety of cellular functions by coupling cell metabolism with membrane potential. Kir6.1, Kir6.2 and SUR2A were expressed in undifferentiated MSC, whereas SUR2B and SUR1 were not detected on cDNA and protein level. Upon adipogenic differentiation Kir6.1 and SUR2A showed a significant reduction of the amount of mRNA by 84% and 95%, respectively, whereas Kir6.2 expression was unchanged. Osteogenic differentiation strongly up-regulated Kir6.2 mRNA (28-fold) whereas Kir6.1 and SUR2A showed no significant change in expression. Quantitative Western blot analysis and immunofluorescence staining confirmed the elevated expression of Kir6.2 upon osteogenic differentiation. Taken together, expression changes of KATP channels may contribute to in vitro differentiation of MSC and represent changes in the metabolic state of the developing tissue.
Im Titel ist "ATP" bei K tiefgestellt
Gesehen am 30.05.2022